Weathering of unsaturated waste rocks from Kevitsa and Hitura mines: Pilot-scale lysimeter experiments and reactive transport modeling. (July 2021) - Muniruzzaman, Muhammad; Karlsson, Teemu; Ahmadi, Navid; Kauppila, Päivi M.; Kauppila, Tommi; Rolle, Massimo
Abstract: The fundamental understanding of hydrogeochemical processes leading to toxic drainage in mining environments is of utmost importance to predict the impact of mining activities in waste facilities and to design effective measures for the mitigation of environmental risk. This study investigates the weathering behavior of different types of mine waste rocks, with considerably different mineralogical and textural properties, by performing long-term (>3 years) pilot-scale lysimeter experiments combined with multiphase and multicomponent reactive transport modeling. The experiments were carried out in a series of five lysimeter setups, packed with unsaturated waste rocks collected from the Kevitsa and Hitura mine sites in Finland, under the influence of outdoor atmospheric conditions. We focus on the temporal dynamics of the waste rock effluents' chemistry showing remarkably different compositions in different experiments. The low-sulfide containing Kevitsa pyroxene and Hitura serpentinite waste rocks lead to alkaline drainage, characterized by higher pH (up to 9.5) and lower dissolved constituents (e.g., up to 420 mg/L SO4, 89 μg/L Ni). In contrast, the effluents from the Hitura mica schist waste rocks, which have relatively higher sulfide abundance, show characteristics of acidic drainage with lower pH ( 4.3) and orders of magnitude higher aqueous concentrations (e.g., up to 3100 mg/L SO4, 130 mg/L Ni). The results also show that the presence of a higher fraction of finer particles leads to a faster dissolution rate and thus relatively higher drainage concentrations. The experimental results were quantitatively interpreted with multiphase and multicomponent reactive transport modeling, which allowed capturing the complex dynamic trends and the concentration levels observed in the effluents of the different pilot-scale lysimeters. Graphical abstract: Image 1 Highlights: Long-term lysimeter experiments to study the weathering of different waste rocks. Distinct textural and geochemical properties of the waste rocks from two mine sites. Acidic and alkaline drainage with different compositions from five lysimeters. Multiphase and multicomponent reactive transport modeling of the experiments.